FACTORS AFFECTING FIRM VALUE WITH INSTITUTIONAL OWNERSHIP AS MODERATING VARIABLES IN BANKING COMPANIES LISTED IN INDONESIA STOCK EXCHANGE - Liniarti, Sri (International Journal of Public Budgeting, Accounting and Finance, 2019)
The objective of the research was to examine and to analyse the effect of financial performance (Return on Asset, non-performing loan, capital adequacy ratio, loan to deposit ratio and operational costs on operating income and institutional ownership as moderating variable in banking companies listed on the Indonesia Stock Exchange. This research is  a causal research using secondary data. Populations in this research are 43 banking companies listed in Indonesia Stock Exchange in  the  period 2013-2017. The sampling technique used was census in which all populations were entired for 5 years observations period. The hypothesis was tested by using multiple linear regression analysis and the testing of moderating variable by using absolute difference test. The result shows that simultaneously, financial performance (Return on Asset, non-performing loan, capital adequacy ratio, loan to deposit ratio and operational costs on operating income) affect firm value. Partially, Return on Asset, capital adequacy ratio and operational costs on operating income had positive but not significant effect on firm value, while non-performing loan and loan to deposit ratio had negative and not significant effect on firm value. Moderating variables institutional ownership could not moderate the relationship of financial performance (return on asset and loan to deposit ratio) on the firm value but non-performing loan, capital adequacy ratio and operational costs on operating income could moderate the relationship of financial performance on the firm value.